Context-dependent differences in the functional responses of Lactobacillaceae strains to fermentable sugars - Suissa, Ronit; Oved, Rela; Maan, Harsh; Hadad, Uzi; Gilhar, Omri; Meijler, Michael M.; Koren, Omry; Kolodkin-Gal, Ilana (Frontiers in Microbiology, 2022)
Lactobacillaceae are Gram-positive rods, facultative anaerobes, and belong to the lactic acid bacteria (LAB) that frequently serve as probiotics. We systematically compared five LAB strains for the effects of different carbohydrates on their free-living and biofilm lifestyles. We found that fermentable sugars triggered an altered carrying capacity with strain specificity during planktonic growth. In addition, heterogeneous response to fermentable sugar was manifested in microbial aggregation (measured by imaging flow cytometry), colony development, and attachment to mucin. The acid production capacities of the strains were compatible and could not account for heterogeneity in their differential carrying capacity in liquid and on a solid medium. Among tested LAB strains, L. paracasei, and L. rhamnosus GG survived self-imposed acid stress while L. acidophilus was extremely sensitive to its own glucose utilization acidic products. The addition of a buffering system during growth on a solid medium significantly improved the survival of most tested probiotic strains during fermentation, but the formation of biofilms and aggregation capacity were responsive to the carbohydrate provided rather than to the acidity. We suggest that the optimal performance of the beneficial microbiota members belonging to Lactobacillaceae varies as a function of the growth model and the dependency on a buffering system.